ACADEMICS COMPOUNDING HINDUTVA - Sivaramkrishna, M. 1935- (2004)
‘Hindutva’ exists in two major contexts: the first consists of academic studies, in and from the ‘West’, regarding virtually every aspect of Hinduism. To this category belong also, collateral studies in India deriving, by and large, from the frames used by the western scholars. The second context is the perennial philosophical tradition of Hinduism consisting of both the sruti and the validation of its truths (or Truths) by the nearly unbroken chain of sages and saints right from the Vedic seers down to Ramakrishna, Ramana Maharshi, and more recently Nisargadatta and others. The paradox is that the first category has little to do with the second. For many reasons, the main one constituted by the experiences of these seers is regarded, in the eyes of the academics, teleological and highly subjective.
Keywords: Hinduism; Hindutva; Ramakrishna; Religion; The Gospel of Sri Ramakrishna